Analisis Kesulitan Siswa dalam Pemahaman Belajar serta Penyelesaian Masalah Ruang Dimensi Tiga - Lamanda ayuningrum; Arie Purwa Kusuma; Nurina Kurniasari Rahmawati (Universitas Indraprasta PGRI, 2019)
This research includes the kind of qualitative descriptive research aimed at knowing the factors of the cause of the difficulties of the students of class XII SMAN 27 Tangerang District in learning to understand as well as solving three-dimensional geometry problems, particularly point-to-point distances, to lines, and to fields. The subject in this study was 35 academic year students 2019–2020 were selected in purposive sampling. Data collection is done with tests and interviews. The results of the research obtained, among others, a factor of understanding difficulty: 1) Students ' difficulties to imagine or visualize; 2) elaborate teacher explanation; 3) Lack of use of media/props in learning; 4) Students are less concerned with teachers during KBM; 5) low interest in learning; 6) Learning methods are ineffective. The students ' difficulty factor in solving three-dimensional geometry problems, including : 1) do not understand the intent of the question; 2) the wrong image; 3) Low basic understanding of concept calculations; 4) The experience of learning geometry at the previous school level is still lacking.